A systematic cohort review of pheochromocytoma-induced typical versus atypical Takotsubo cardiomyopathy. (15th January 2023) - Aw, Avelyn; de Jong, Mechteld C.; Varghese, Shriya; Lee, James; Foo, Roger; Parameswaran, Rajeev
Abstract: Background: A rare presentation of pheochromocytoma (PCC) is catecholamine-induced-cardiomyopathy, or Takotsubo cardiomyopathy (TCM). PCC-induced TCM(PCC-TCM) can present as a typical or atypical type, based on the location of cardiac wall motion abnormalities. In this review, we sought to assess features and outcomes for PCC-TCM, and to compare typical and atypical subtypes. Methods: A search was conducted on two databases (PubMed and Embase) for case series or reports on PCC-TCM from 2006 to 2020. Results: One-hundred-and-two papers with a total of 104 cases of PCC-TCM were retrieved: 67(64.4%) typical and 37(35.6%) atypical subtypes. Overall median age was 50[range:23–86] years, the atypical group about a decade younger( p  < 0.001). A female preponderance was seen for either subtype (∼75%). The most common presentations were chest pain( n  = 60;58%), dyspnoea( n  = 46;44%), and headache( n  = 41;39.4%). Those with atypical subtype more often presented with fluid overload (typical:3% versus atypical:60%); acute pulmonary oedema (35% versus 60%); and cardiogenic shock (22% versus 43%) (all p  < 0.05). Six patients (6%) died pre-operatively (typical:8% versus atypical:3%; p  = 0.32). Non-fatal pre-operative complications occurred more among those with atypical TCM( p  < 0.001), specifically cardiac arrest (typical:5% versus atypical:32%) and respiratory failure (9% versus 24%; both p  < 0.05). Overall, 98 underwent surgery, majority undergoing laparoscopic adrenalectomy (81%); similar among the subtypes( p  = 0.71). No robust data was provided on short-term outcomes, although two patients suffered from post-operative complications. Conclusion: Although quite similar in presentation to either standalone TCM or PCC, PCC-TCM seems to be associated with a higher degree of morbidity and mortality. The atypical PCC-TCM subgroup seems to have a more severe course with possibly a poorer outcome. Further research is needed to make more reliable inferences. Highlights: Takotsubo cardiomyopathy (TC) is associated with dysfunction of the left ventricle resembling myocardial infarction. The hallmark of the condition is apical hypokinesis of the myocardium with non-obstructed coronary arteries. Pheochromocytoma is an uncommon reversible cause of Takotsubo cardiomyopathy. There appears to be higher degree of morbidity and mortality in pheochromocytoma induced cardiomyopathy. Atypical cardiomyopathy seen in younger patients presents with a more severe clinical course and poorer outcome